L’incidence de la non-acceptance du traitement inhalatoire au niveau de plusieurs points de consultation en Algérie - Chati Halima; Djadj Aicha; Benferhat Hassiba Madjida (Université Amar Télidji Laghouat, 2023)
The public’s perception of inhaled drugs presents a major barrier to the quality of management of asthma, COPD and chronic cough. The main objective of this study is to estimate the frequency of initial refusal to inhalatory treatment and to identify the factors associated with non-acceptance of inhalatory treatment and to study the frequency of the different sources of influence at the non-acceptance to inhalatory treatment. First, It was a prospective descriptive study involving 385 patient consultants at several points of private and state consultations in Algeria, during a period from 01 November 2022 to 31 January 2023. The average age was 40.12 years for our entire study population and with extremes ranging from 4 months to 97 years. The incidence of initial refusal of inhalatory treatment was estimated at 32.99% (CI: 28.31 to 37.93),Moreover, it was found that 78.44% of inhalatory treatment prescribed for consulting patients was in spray form, and it was also noted that treatment in capsule form was refused month with easy acceptance to inhaled long-acting beta-2-mimetic treatment. In our study the majority of consulting patients at the consulting center level were attient of asthmatic disease 73.25%. It was noted that the main cause of refusal of inhalatory treatment marked by patients was the fear of dependence 55.12%, and the main source of influence was the patient’s close entourage 40.52% of all subjects initially refusing inhalatory treatment. There has been a high frequency of initial refusal to inhalatory treatment in consulting patients due to lack of therapeutic education, hence the high rate of therapeutic non-acceptance and, The role of close relatives and the media as sources influencing the acceptance of the disease and adherence to treatment has been advocated
30cm CD-ROM